The effectiveness of the low-level laser, antibiotic and surgical therapy in the treatment of medication-related osteonecrosis of the jaws: A case report - Del Pilar Rodríguez-Sánchez, Maria; Statkievicz, Cristian [UNESP]; de Mello-Neto, João Martins [UNESP]; Toro, Luan Felipe [UNESP]; Bassi, Ana Paula Farnezi [UNESP]; Garcia, Valdir Gouveia [UNESP]; Theodoro, Letícia Helena [UNESP]; Ervolino, Edilson [UNESP] (Maad Rayan Publishing Company, 2020)
Introduction: Bisphosphonates consist of a range of drugs used in the treatment of osteopathy or some osteotropic malignancies. Medication-related osteonecrosis of the jaw (MRONJ) is a serious adverse consequence of their use. Conventional treatment is not always effective, so it is necessary to resort to the use of adjuvant therapies. This study aimed to evaluate the effectiveness of the association of surgery, antibiotic therapy and low-level laser (LLL) therapy as a treatment strategy for MRONJ through the presentation of a clinical case. Case Presentation: A 49-year-old female patient presented for the diagnosis and treatment of bone lesions in the maxillae. The patient reported that she had used zoledronate for 1 year. Five years later there were 2 painless bone lesions on both sides of the maxilla, following the extraction of the first upper molars. Clinical, tomographic and histopathologic examination established the diagnosis of MRONJ. The treatment consisted of the curettage of the necrotic bone, antibiotic and thirteen LLL therapy sessions. Integral mucosal healing was observed after a two-month follow-up and no symptoms were detected. The patient was evaluated at 6 and 12 postoperative months without complications. Conclusion: The combination of surgery, antibiotic therapy, and LLL therapy has shown to be effective in the treatment of MRONJ.
Keywords: Anti-bacterial agents; Diphosphonates; Laser therapy; Oral surgical procedures; Osteonecrosis